STRATEGI PENGEMBANGAN WISATA ALAHAN PANJANG DALAM MENDORONG PEMBANGUNAN DAERAH BERKELANJUTAN - Rafi; Zaitul Ikhlas; Boni Saputra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the tourism development strategy in Alahan Panjang in fostering sustainable regional development. The research method employed is a qualitative approach with a descriptive research design conducted through a literature review (library research). The data used consists of secondary data obtained from scientific journals, books, and official documents related to tourism and sustainable development. Data analysis was performed descriptively and qualitatively using a SWOT analysis approach to identify strengths, weaknesses, opportunities, and threats in tourism development. The results of the study indicate that Alahan Panjang possesses significant tourism potential, particularly regarding natural beauty, such as Danau Diatas and Danau Dibawah, as well as agro-tourism and local culture potential. However, tourism development still faces various constraints, including infrastructure limitations, low human resource quality, lack of promotion, and threats to environmental sustainability. Recommended development strategies include strengthening nature-based tourism attractions with an eco-friendly approach, improving the quality of facilities and services, empowering local communities, and optimizing digital promotion.